KUALITAS TUMBUH KEMBANG, PENGASUHAN ORANG TUA, DAN FAKTOR RISIKO KOMUNITAS PADA ANAK USIA PRASEKOLAH WILAYAH PEDESAAN DI BOGOR - Latifah, Melly; Alfiasari, Alfiasari; Hernawati, Neti (Jurnal Ilmu Keluarga dan Konsumen, 2009)
Every family wants to reach qualified children in conducting of child caring. Generally, this study aims to analyze: (i) quality of child development; (ii) quality of psychosocial environment of parenting practices; and (iii) quality of family life and community that identified become risk factors to child development. This article is a part of results of multiyears study that consists of data from first year study. The design of the first study is cross sectional study that involved 208 families in rural area who had preschool children. The sites of study are four villages in two sub districts (Ciawi and Ciampea) in Bogor. The sites chosen by purposive based on the ecological context. Meanwhile, the samples are chosen by random sampling the result of this study showed that in all of study sites, only 70% of the children that had high quality of developmental task. The other result showed that there were 71,6% families in Ciawi and 64,2% in Ciampea that had moderate quality of psychosocial environment of parenting practices. The level of stress and anxiety of mother gave significant negative effect to quality of parenting. There are some factors that identified will become risk factors of community to child development such as communication low level of education, low income, and low knowledge of parenting.